Pelatihan dan Pendampingan bagi Pelajar Tunanetra untuk Epeningkatan Aksesibilitas Pembelajaran Sejarah Kota Makassar - Azisah, Andi Balqis Mutiara; Taufiq, Maura Sabrina; Al Resky, Muh. Ibnu Ammar; Syarif, Muhammad; Lindasari, Lindasari; Aris, Valentino (Penerbit Goodwood, 2024)
Purpose: History is a science that is very important for human development, culture and technology which we can enjoy today. This Community Service aims to increase accessibility for blind students in learning history, especially history related to Makassar City. Methodology: This Community Service Activity is carried out using methods namely preparation, socialization, training, mentoring and sustainability evaluation. Results: The results of the pre-test and post-test showed that there was a significant increase in the knowledge of the training participants regarding history where the average score before the training was given was 28 and after the training was given it increased significantly to an average of 92.2. The results of the training are also implemented in the form of an arts festival, where training participants display the results of the training in the form of drama, reading poetry and singing regional songs. Conclusions: The results of this community service activity have proven to enhance the participants' knowledge regarding the history related to the city of Makassar. This is evident from the post-test results, where all participants had a good understanding of the history related to Makassar. The use of braille books and audiobooks was also very appropriate, as it helped increase the participants' interest and acceptance of the material provided. The participants were able to implement the material in the form of a performance of arts and culture. The performance they carried out was an application of the material provided to the participants during the training and mentoring process. Limitations: The limitations of this community service activity are the limited number of participants, limited books, and information retrieval during the pre-test and post-test. Contribution: The results of this service activity can increase the accessibility of blind students in learning history.